Mathematical modeling and cost comparison for electricity generation from petrol and liquified petroleum gas (LPG) - Lawal M. Olalekan; Oladepo Olatunde; Faleti I. Olufemi; Amodu A. Olamide (Universitas Muhammadiyah Magelang, 2022)
This study investigates and compares the cost of generating electricity from petrol and liquified petroleum gas (LPG) gas using a 2.5 kVA, 50Hz Elepaq generator. It also develops mathematical models that can be used to predict important parameters of the generator The generator is connected with a multi-fuel carburetor in the experimental setup, allowing both fuel sources to be fed alternatively. The electric bulbs of different ratings were connected and varied as load. The generator was first run using petrol. The time used to exhaust half litres of petrol was recorded. It was then run with LPG for a period equal to the time of run on petrol, taking note of the mass of LPG consumed. A cost comparison was carried out and mathematical models were developed for both fuels usage using MATLAB “polyfit” command. The results show that with less or equal 1350W connection of purely resistive load. It is more economical to run the generator using LPG. However, at any load beyond 1350 W, it is economical to run the generator using petrol. The two models developed best fit the experimental results obtained with a correlation of 0.9869 and 0.9962.